1987
DOI: 10.1111/j.1432-1033.1987.tb13543.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of the soluble form of the junctional plaque protein, plakoglobin, from different cell types

Abstract: A polypeptide of identical molecular mass ( M , 83 000) and charge to desmosomal plakoglobin from bovine snout epidermis was identified in soluble and pelletable fractions from diverse tissues and cells of different mammalian species, including cells and tissues devoid of desmosomes (e. g. endothelial, retinal, lenticular cells, fibroblasts). The protein, however, wdS not detected in erythrocytes and platelets and in myeloma cells, nor in smooth muscle tissue. In all cells examined, the plakoglobin soluble upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 72 publications
2
44
0
Order By: Relevance
“…Proteins of the 100,000 g supernatant fraction described above were concentrated by vacuum dialysis against near-physiological salt buffer to a final volume of 500 Ixl (33,34,60). These samples were then loaded on top of 'x,l 1 ml of a 5-30% (wt/vol) continuous sucrose gradient and centrifuged in a Beckman SW40 rotor at 35,000 rpm for 18 h at 5°C.…”
Section: Sucrose Gradient Centrifugationmentioning
confidence: 99%
“…Proteins of the 100,000 g supernatant fraction described above were concentrated by vacuum dialysis against near-physiological salt buffer to a final volume of 500 Ixl (33,34,60). These samples were then loaded on top of 'x,l 1 ml of a 5-30% (wt/vol) continuous sucrose gradient and centrifuged in a Beckman SW40 rotor at 35,000 rpm for 18 h at 5°C.…”
Section: Sucrose Gradient Centrifugationmentioning
confidence: 99%
“…At the molecular level, it has been shown that, although the two subfamilies share some molecular constituents (i.e., vinculin, a-actinin, and actin), there are some components that are specific for each of them. The cytoplasmic plaque molecule talin (Burridge 1983a,b) and the integrin ECM receptors (Damsky et al, 1985) were shown to be specific for cell-matrix AJ, whereas the plaque molecule plakoglobin (Kapprell et al, 1987) and the transmembrane receptors of the cadherin family (Takeichi, 1988) are uniquely associated with cell-cell AJ. Still poorly understood are the regulatory mechanisms that control AJ formation and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, modification of plakoglobin and ␤-catenin appears to be dependent on the cell context. Epidermis has many layers of non-proliferating cells that contain a significant cytosolic fraction of plakoglobin (62). Similarly 293T cells do not proliferate following transient transfection and the expressed plakoglobin is mostly cytoplasmic because of lack of cell junctions in this cell line (11).…”
Section: Resultsmentioning
confidence: 95%